Trees, Trade and Textiles: Potash Imports and Ecological Dependency in British Industry, c.1550–1770. Issue 1 (11th April 2018) - Warde, Paul
Abstract: This article charts the development of the trade in a key input into early modern British industry: potash, used as a source of alkali, predominantly in the making of soap for washing woollens, and the bleaching the linen. Although an essential intermediary input into the manufacturing processes through precursors to the modern chemical industry, this trade and its ecological impact have gone almost entirely unnoticed by historians. The article sets out the scale of the trade and its organization reaching to regions of supply in the Baltic and Russia, before a rapid switch towards North American suppliers after 1760. Knowledge of the potash trade expands the scope and understanding of the 'organic economy' to a product that accounted for the largest share of 'ghost acres' abroad used to underpin British industrial development and whose wood requirements came to far exceed the production of wood within Britain. Data on the ash trade provides an indicator for the scale of industrial output, and relative size of the textile-finishing sector in England and the Netherlands that may modify our understanding of the relative fortunes of industries in both countries.